Impact of psycho-cognitive factors on managerial decision-making the case of human resources managers - Benmoussa, Samir; Bouziane, Mourad (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Business decision is the heart of management. His study requires the intervention of several paradigms of understanding, in fact, mathematics, economics, political science and psychology are interested in this complex cognitive process. This article aims to highlight the dynamics of "decision-making" while presenting a literature review on the role of "emotional intelligence" and "self-efficacy" as factors psycho cognitive that can intervene in the decision-making process at the HR manager.